Gut Bacteria Erysipelatoclostridium and Its Related Metabolite Ptilosteroid A Could Predict Radiation-Induced Intestinal Injury - Cai, Shang; Yang, Yongqiang; Kong, Yuehong; Guo, Qi; Xu, Yingying; Xing, Pengfei; Sun, Yanze; Qian, Jianjun; Xu, Ruizhe; Xie, Liwei; Hu, Yijia; Wang, Min; et al. (Frontiers in Public Health, 2022)
It is difficult to study the intestinal damage induced by space radiation to astronauts directly, and few prediction models exist. However, we can simulate it in patients with pelvic tumor radiotherapy (RT). Radiation-induced intestinal injury (RIII) is common in cancer patients who receieved pelvic and abdominal RT. We dynamically analyzed gut microbiota and metabolites alterations in 17 cervical and endometrial cancer patients after pelvic RT. In patients who later developed grade 2 RIII, dysbiosis of gut microbiota and metabolites were observed. Univariate analysis showed that Erysipelatoclostridium and ptilosteroid A were related to the occurrence of grade 2 RIII. Notably, a strong positive correlation between gut bacteria Erysipelatoclostridium relative abundance and gut metabolite ptilosteroid A expression was found. Furthermore, combinations of Erysipelatoclostridium and ptilosteroid A could provide good diagnostic markers for grade 2 RIII. In conclusion, gut bacteria Erysipelatoclostridium and its related metabolite ptilosteroid A may collaboratively predict RIII, and could be diagnostic biomarkers for RIII and space radiation injury.